Stigma, housing and identity after prison. Issue 4 (July 2018) - Keene, Danya E.; Smoyer, Amy B.; Blankenship, Kim M.
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.